EFFECTIVENESS OF GELATIN TANNATE IN ACUTE INFECTIOUS DIARRHEA IN CHILDREN - M. K. Bekhtereva; A. M. Komarova; A. N. Uskov; I. V. Razdyakonov; L. A. Alekseeva; T. V. Bessonova (LLC "Diagnostics and Vaccines", 2017)
Specific features of the course of acute intestinal infections of viral and bacterial etiology in children are described, features of the syndrome of endogenous intoxication in children carrying infectious diarrhea are characterized. As a result of the study, the efficacy and safety of gelatin tannate (LLC «YADRAN», Croatia) with intestinal infections of bacterial and viral etiology in children has been confirmed.